IJCM_46A: Attendance in Anganwadi centres through Anganwadi workers' lens: A Force Field Analysis in Urban slum - Raul Mayuri (Wolters Kluwer Medknow Publications, 2024)
Background: The NFHS-5 found that 35.5% (Urban areas-30%) of children under five years were stunted and 32.1% were overweight (1). ICDS being a centrally sponsored scheme, is functioning nationwide in tribal, rural and urban slums; with a potential to improve nutritional outcome as well as overall development of the child. Children dwelling in urban slums are at a higher risk of being undernourished. As per the NFHS 2015-16 survey, only 40.2% of children from urban areas are receiving ICDS services. The anganwadi workers(AWW) identify and encourage the beneficiaries to attend anganwadi regularly and avail the services. Objective: The aim of this study was to understand the reasons for a lower enrolment of children in anganwadi. Methodology: The study was conducted in an urban slum in Mumbai with a population of 1.2lakh. We conducted force field analysis among the AWWs in 3 groups of 6-7 each. The factors mentioned in individual sheets and those represented in diagram were analysed manually. Results: The force field analysis revealed that the motivating factors for attending anganwadi regularly were closer distance from home, attractive toys/activities, special food on certain days, interactive teachers, meeting friends, siblings going to school. On the contrary, reasons for poor/nil attendance were infrastructural challenges like restricted space, no water and electricity, rented anganwadis; availability of private/municipality preschools nearby; working parents; ration made available at doorsteps during COVID and disinterest in the variety of food provided. Conclusion: Need-based revamping of Anganwadis in urban slums is needed to improve the attendance of children and in turn ensure good nutrition and development of children in slums.